ASSOCIATION BETWEEN PSYCHOSOCIAL FACTORS AND SUICIDAL BEHAVIOR IN PATIENTS WITH BIPOLAR DISORDER CURRENT EPISODE DEPRESSION (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the association between several psychosocial factors and suicidal behavior in patients with bipolar disorder current episode depression.Methods: A cross-sectional descriptive study using convenience sampling method.Results: Several psychosocial factors were significantly associated with suicidal behavior. These factors included recent psychological stress or trauma (OR = 6,516; p = 0,001), childhood trauma (OR = 5,471; p = 0,012), lack of reasons and purpose in life (OR = 2,455; p = 0,029), and dissatisfaction with current life (OR = 3,896; p = 0,002).Conclusion: Suicidal behavior is relatively common among patients with bipolar disorder during depressive episodes. Certain psychosocial factors, such as lack of a reason or purpose in life and dissatisfaction with current life, are associated with an increased risk of suicidal behavior in this patient group.
Keywords: Bipolar disorder, depression, suicidal behavior, psychosocial factors.